"And Who Is My Brother?" The Scope of Religious Communitarianism in Europe. (October 2017) - VanHeuvelen, Tom; Robinson, Robert V.
Analyzing 40 countries in the 2008–2009 European Values Study (EVS), we test hypotheses that three religion dimensions—religious orthodoxy (believing), involvement in religious services and organizations (behaving), and affiliation with religious traditions (belonging)—are associated with economic communitarianism as opposed to individualism and with extending economic concern universalistically to all social categories. The EVS assesses respondents' concern for the living conditions of social categories ranging from their immediate family to all humankind, as well as for vulnerable social categories—the elderly, the sick and disabled, poor children, the unemployed, and immigrants. While we find that Protestants are in some respects limited and exclusive in extending economic communitarianism, two of the most important factors in concern for the well-being of others and in universalistically extending this are religious orthodoxy and involvement in religion. Moreover, the orthodox and the religiously involved are more likely to express concern for the well-being of immigrants. We conclude that people of faith are far less exclusive and particularistic than less religious people in their economic concern for others, suggesting they could support welfare state efforts within their countries, bailouts to help weaker economies in Europe, and foreign aid to improve the conditions of those living in poorer countries.